Confirmatory Faktor Analisis Fluktuasi Harga Obligasi Pada Perusahaan Perbankan Indonesia - Fitra Arlina Nasution (Fisarrearch, 2021)
This investment is made to finance the company's operations through the issuance of shares and bonds. Judging from Indonesia's investment opportunities every year, the average investment opportunity has increased from year to year. Investment in financial assets is the type of investment that is most often made by investors, because it is generally intangible but still has a high value. One example of a financial asset traded on the bond stock exchange is. The main reason is that many investors are attracted to bonds because bonds provide a fixed yield (return) over a relatively long period of time and do not affect interest rate fluctuations. In addition, investors want the security of their invested capital through high quality bonds. Credit interest rates, inflation rates, curves, leverage as measured by debt to equity ratio (DER), firm size and profitability as measured by return on assets (ROA) and debt to asset ratio (DAR) are very influential on the ups and downs bond. This study aims to determine whether credit interest rates, inflation rates, exchange rates, leverage, firm size, profitability and debt-to-asset ratios have a significant effect on bond prices in companies, either partially or simultaneously. The data from this study were obtained from the financial statements of the Go Public Property companies listed on the Indonesia Stock Exchange. The sample of this research is 18 banking companies listed on the Indonesia Stock Exchange and data from 2013 – 2017. The determination of the sample uses the purposive sampling method. The type of data used is secondary data with the media in the form of audited financial statements of companies listed on the Indonesia Stock Exchange. The results show that the inflation rate and leverage partially have no significant effect on bond prices, while DAR partially has a significant effect on bond prices in banking companies listed on the Indonesia Stock Exchange. Inflation rate, leverage and DAR simultaneously have a significant effect on bond prices in banking companies listed on the Indonesia Stock Exchange.